Meningkatkan Kemampuan Motorik Kasar Melalui Permainan Bowling Pada Anak Usia Dini di TK Garuda Manado - Threesje Tolukun (Peneliti.net, 2023)
This study aims to improve gross motor skills, especially in the components of coordination, accuracy and balance through bowling. This research is a classroom action research. The subjects of this study were the children of group B1 TK Garuda Manado for the 2022/2023 school year, which consisted of 15 children. The object of this study is the improvement of children's gross motor skills through bowling games. The data collection is through observation and documentation. Data were analyzed by descriptive quantitative and descriptive qualitative. The results showed that gross motor skills increased through bowling which was supported by components of physical fitness including: coordination, accuracy and balance. Learning activities in Sikus I are carried out by first introducing children to the game of bowling, then the teacher gives examples of playing bowling correctly to children, so that children can understand learning activities through bowling games. In Cycle II the implementation of the action was carried out based on solving the problems that emerged in Cycle I such as providing more specific motivation and guidance to children so that learning activities through bowling games could be further increased according to the indicators of success to be achieved. This can be seen from the results of observations at pre-action, children who got very good criteria 2 children (13.3%). In Cycle I, there were 4 children (26.7%) who got very good criteria and in Cycle II, there were 13 children (86.7%) who got very good criteria.